Negotiating Religious Moderation In The Digital Sphere: Digital Literacy, Gender Gaps, and Radicalism Exposure Among Pesantren Students - Rindha Widyaningsih; JM Muslimin; Francisco Villacampa Megía (Edukasia Islamika : Jurnal Pendidikan Islam, 2026)
The digital globalization phenomenon has strengthened the role of online media in the spread of various ideas, including radicalism, which poses a significant challenge for Islamic boarding schools as centers of Islamic education. This research aims to evaluate students' digital literacy in addressing radicalism and to analyze variation in literacy levels by region and gender across six provinces on the island of Java. The research method used is a quantitative survey. The methodological stages consist of: (1) validation and reliability of digital literacy instruments based on the Ministry of Communication and Information framework; (2) determination of the population and equitable distribution of student samples by stratified random sampling in six regions; (3) data collection through a constructed online questionnaire; (4) systematic data processing through coding and cleaning; and (5) descriptive statistical analysis, comparison of mean and standard deviation scores, and score categorization for each demographic and gender variable. The study's results indicate that students are predominantly categorized as having "Intermediate" and "high" digital literacy levels across all regions. By gender, female students were more likely to be in the "high" category (31.5%) than male students (27.7%), while the "Intermediate" category was almost equally represented in both groups. However, the "low" and "very low" categories persist across all groups and regions, indicating that digital literacy challenges remain to be addressed. The implications of this study emphasize the need to integrate digital literacy into the curriculum and culture of pesantren education in a way that is responsive to current issues. Adaptive digital literacy programs have the potential to develop students' critical thinking skills, enhance their resilience to online radicalization, and foster religious moderation in the digital era.